Molecular evidence for sex reversal in wild populations of green frogs (Rana clamitans) - Max R. Lambert; Tien Tran; Andrzej Kilian; Tariq Ezaz; David K. Skelly (PeerJ, 2019)
In vertebrates, sex determination occurs along a continuum from strictly genotypic (GSD), where sex is entirely guided by genes, to strictly environmental (ESD), where rearing conditions, like temperature, determine phenotypic sex. Along this continuum are taxa which have combined genetic and environmental contributions to sex determination (GSD + EE), where some individuals experience environmental effects which cause them to sex reverse and develop their phenotypic sex opposite their genotypic sex. Amphibians are often assumed to be strictly GSD with sex reversal typically considered abnormal. Despite calls to understand the relative natural and anthropogenic causes of amphibian sex reversal, sex reversal has not been closely studied across populations of any wild amphibian, particularly in contrasting environmental conditions. Here, we use sex-linked molecular markers to discover sex reversal in wild populations of green frogs (Rana clamitans) inhabiting ponds in either undeveloped, forested landscapes or in suburban neighborhoods. Our work here begins to suggest that sex reversal may be common within and across green frog populations, occurring in 12 of 16 populations and with frequencies of 2–16% of individuals sampled within populations. Additionally, our results also suggest that intersex phenotypic males and sex reversal are not correlated with each other and are also not correlated with suburban land use. While sex reversal and intersex are often considered aberrant responses to human activities and associated pollution, we found no such associations here. Our data perhaps begin to suggest that, relative to what is often suggested, sex reversal may be a relatively natural process in amphibians. Future research should focus on assessing interactions between genes and the environment to understand the molecular and exogenous basis of sex determination in green frogs and in other amphibians.